Lipid-Based Nutrient Supplements Providing Approximately the Recommended Daily Intake of Vitamin A Do Not Increase Breast Milk Retinol Concentrations among Ghanaian Women. Issue 2 (6th January 2016) - Klevor, Moses K; Haskell, Marjorie J; Lartey, Anna; Adu-Afarwuah, Seth; Zeilani, Mamane; Dewey, Kathryn G
Abstract: Background: Vitamin A deficiency remains a global public health problem. Daily supplementation with a lipid-based nutrient supplement (LNS) has potential for increasing milk vitamin A concentrations. Objective: The objective of this study was to determine whether daily supplementation with approximately the recommended daily intake of vitamin A in an LNS or a multiple-micronutrient supplement (MMN) during pregnancy and the first 6 mo postpartum has an effect on breast milk retinol concentration at 6 mo postpartum. Methods: Women ≤20 wk pregnant ( n = 1320) were randomly assigned to receive either the MMN providing 18 micronutrients, including 800 μg retinol equivalents of vitamin A, or the LNS with the same nutrients as the MMN group, plus 4 minerals and macronutrients, until 6 mo postpartum; a control group received iron and folic acid during pregnancy and a placebo (calcium tablet) during the first 6 mo postpartum. Breast milk samples collected at 6 mo postpartum were analyzed for retinol and fat concentrations by HPLC and creamatocrit, respectively, in a subsample of 756 women. Results: The breast milk retinol concentration was (mean ± SD) 56.3 ± 2.1 nmol/g fat, with no significant differences between groups [iron and folic acid ( n = 243): 59.1 ± 2.8; MMN ( n = 260): 55.4 ± 2.5; LNS ( n = 253): 54.7 ± 2.5 nmol/g fat; P = 0.45], regardless of whether the woman had or had not received a high-dose vitamin A supplement (200, 000 IU) soon after childbirth. Around 17% of participants had low milk retinol (≤28 nmol/g fat). We estimated that 41% of infants were potentially receiving vitamin A at amounts above the Tolerable Upper Intake Level (600 μg retinol activity equivalents/d), with no group differences in percentages with low or high milk retinol concentration. Conclusion: Daily consumption of approximately the recommended intake of vitamin A did not increase breast milk retinol concentrations in this sample of Ghanaian women. This trial was registered at clinicaltrials.gov as NCT00970866.